Impact of blood centrifugation on the parameters of thrombin generation assay revisited to look for possible revision of the current guidance - Erica Scalambrino; Marigrazia Clerici; Flora Peyvandi; Armando Tripodi (Practical Laboratory Medicine)
Blood centrifugation affects thrombin generation assays (TGA). Current guidance recommends double-centrifugation, which is uncommon in clinical laboratories.We evaluated the impact of 4 centrifugation speeds on TGA performed with low-triggers (1pM tissue-factor/1.0 μM phospholipids) or high-triggers (5pM tissue-factor/5.0 μM phospholipids). TGA parameters were evaluated in the presence/absence of thrombomodulin.We included 20 healthy subjects. Centrifugation speeds were: (i)Double-centrifugation: blood at 2,500g(15min) and plasma at 2500(15min) (reference method). (ii)Single-centrifugation at 3,000g(20min). (iii)Single-centrifugation of blood at 3,000g(20min), plasma freezing, then centrifugation of thawed plasma at 10,000g(5min). (iv)Single-centrifugation at 1,700g(10min). Results were also expressed as percentage difference relative to reference centrifugation.Lag-time was affected when centrifugation speed was relatively slow (1,700g), regardless of low- or high-triggers, presence or absence of thrombomodulin, whereas it was scarcely affected by centrifugation at 3,000g. Peak-thrombin was marginally affected at relatively low-speed (1,700g). ETP was marginally affected at relatively low-speed (1,700g), except when TGA was performed in the presence of thrombomodulin. Peak-thrombin and ETP were not or were poorly affected by centrifugation at 3,000g or 10,000g after thawing, respectively.In conclusion, slow-centrifugation (1,700g) had a considerable impact on lag-time. This centrifugation speed represents common practice in clinical laboratories and should not be used for TGA, unless controls samples centrifuged at the same speed are used for comparison. Single-centrifugation at 3,000g may be a suitable alternative, which would allow TGA testing without the complex and time-consuming double-centrifugation as recommended by current guidance. We propose that current guidance on plasma preparation for TGA be switched from double-to a more intense single-centrifugation.